Inoculation with mycorrhizal fungi modifies praline metabolism and increases chromium tolerance in pepper plants (Capsicum annuum L.) - Ruscitti, Marcela (2011)
In general, heavy metals interfere with several physiological processes and reduce plant growth. Plants naturally establish symbiotic associations with soil microorganisms, such as mycorrhizal fungi. The aim of this research was to determine if inoculation with mycorrhizal fungi increases tolerance to Cr, evidenced by growth and biochemical parameters and the effect on roots membranes in Capsicum annum. Plants were either non-inoculated or inoculated with Glomus mosseae or Glomus intraradices, and grown in the presence of different concentration of Cr (K2Cr2O4) in soil. Pepper plants grown without Cr behaved as mycotrophic species. At the highest concentration (200 μM K2Cr2O4), Cr reduced root colonization by G. mosseae or G. intraradices (to 23 and 20% respectively). Moderate and high concentrations of Cr reduced all growth parameters. The interaction of inoculation and Cr increased leaf chlorophyll and proline content while reduced the leaf protein and root proline content. Carotenoid content was not affected by treatments. High Cr concentrations increased significantly electrolytes leakage in roots, either non-inoculated or inoculated plants. At the highest Cr concentration, inoculated plants had double the biomass of non-inoculated plants. Cr content in roots of inoculated plants was significantly higher than in non-inoculated plants. Chromium accumulation was low in leaves and showed no differences between treatments. Mycorrhization increased pepper plant tolerance to Cr in the soil, modifying proline metabolism to assure a more efficient response.